A comprehensive bulk chlorine decay model for simulating residuals in water distribution systems. Issue 4 (21st April 2017) - Fisher, Ian; Kastl, George; Sathasivan, Arumugam
Abstract: Chlorine decay models provide efficient ways to develop disinfection strategies for water distribution systems, provided they account separately for bulk and wall decay, and accurately describe decay with a single set of coefficients. The augmented two-reactant (2RA) model is shown to be the simplest model to accurately describe effects of rechlorination dose/timing on bulk chlorine decay, in combination with effects of initial concentration and temperature over long periods. The two-reactant (2R) and variable reaction-coefficient (VRC) models provided predictions of comparable accuracy under higher and successive rechlorination doses at constant temperature. However, the 2RA model provides a more general basis for strategy development, as the VRC model cannot describe the effect of temperature variation. The minimal data-set required for 2RA calibration was similar for all cases considered. The 2RA model is readily applied by incorporation into system modelling software such as the multi-species extension (MSX) to EPANET software.